Fabrication temperature sensing by using ZnO Nanoparticles - Khudiar, Ausama I. (University of Thi-Qar Journal of Science, 2019)
A present study is reported for the synthesis and characterization of ZnO nanoparticles and its application as a temperature sensor. ZnO nanoparticles thin film was prepared the by Sol: Gel method and deposition on a glass substrate. Structural and optical properties of ZnO films were studied. Structural investigation including microstructure was carried out by X-ray diffraction (XRD) analysis. The films gave a hexagonal wurtzite structure. Optical properties of the thin films were determined by using UV-Vis spectrometer. It was found the value of the band gap of the thin film is 3.18 eV. The variations in resistance of sensing with different temperatures were recorded. The relative resistance was decreased linearly with increasing temperature over the range (120- 250)°C.